Internet censorship detected in Pakistan (Pakistan) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Pakistan. Data sourced from CensoredPlanet.
Censorship Incident ID: PK-2026-0432. Severity: warning. Confidence: 65%